Новые среднеазиатские виды чехлоносок группы Coleophora vibicella Нb. (Lepidoptera, Coleophoridae) с кустарниковых астрагалов - Фалькович, M.И. (Вестник зоологии, 1973)
Casebearer species close to Coleophora vibicella 11 b. are a natural complex connected with the plants of Fabaceae and Asteraceae. Four desert species of this group (Coleophora astragalorum sp. n., C. albens sp. n., C. singreni sp. n. and C. eucoleos sp. n.) living on shrub forms of Astragalus (Astragalus villosissimus and A. unifoliolatus) in Bukhara region are described.